2014
DOI: 10.1007/s00253-014-6135-3
|View full text |Cite
|
Sign up to set email alerts
|

Nattokinase: production and application

Abstract: Nattokinase (NK, also known as subtilisin NAT) (EC 3.4.21.62) is one of the most considerable extracellular enzymes produced by Bacillus subtilis natto. The main interest about this enzyme is due to its direct fibrinolytic activity. Being stable enough in the gastrointestinal tract makes this enzyme a useful agent for the oral thrombolytic therapy. Thus, NK is regarded as a valuable dietary supplement or nutraceutical. Proven safety and ease of mass production are other advantages of this enzyme. In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 86 publications
0
62
0
Order By: Relevance
“…Nattokinase is considered to be a safe, powerful, low cost, and all-natural supplement for the treatment of heart and cardiovascular disease [5,6,7]. Animal [3,4,8] and human trials [9,10,11] have demonstrated that NK provides support to the circulatory system by thinning the blood and dissolving blood clots.…”
Section: Benefits Of Nattokinasementioning
confidence: 99%
See 1 more Smart Citation
“…Nattokinase is considered to be a safe, powerful, low cost, and all-natural supplement for the treatment of heart and cardiovascular disease [5,6,7]. Animal [3,4,8] and human trials [9,10,11] have demonstrated that NK provides support to the circulatory system by thinning the blood and dissolving blood clots.…”
Section: Benefits Of Nattokinasementioning
confidence: 99%
“…The mechanism by which NK is transported from the digestive tract into the circulatory system still needs to be elucidated. NK can resist high temperature (50 °C) and pH (to 10), which certainly contributes to the ability of this enzyme to remain intact in the gastrointestinal tract [6]. …”
Section: Benefits Of Nattokinasementioning
confidence: 99%
“…The microscopic morphology was studied under inverted fluorescence microscope (× 400, Axiovert 40CFL, Carl Zeiss, Germany) and the particle size distribution was determined by dynamic light scattering (Mastersizer 2000, Malvern Instruments Ltd., Worcestershire, UK) equipped with a He-Ne laser (k=623 nm), respectively. The results were recorded as the typical volume-weighted mean droplet size D [4,3]. Each formulation was carried out three times in parallel, and data were presented as Mean ± SD.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The results were recorded as the typical volume-weighted mean droplet size D [4,3]. Each formulation was carried out three times in parallel, and data were presented as Mean ± SD.…”
Section: Particle Size Analysismentioning
confidence: 99%
See 1 more Smart Citation